Depression among Tibetan residents in the Southeastern region of Qinghai-Tibet plateau: a cross-sectional study - Yuji Chen; Ga Long; Qing Huang; Ping Zhang; Nie Xu (Scientific Reports)
Abstract Depression has emerged as a significant public health concern, with its prevalence fluctuating based on varying environmental and demographic factors. This study categorized participants based on altitude. A convenient sampling approach was used, and the hamilton depression rating scale-24 was used to assess depressed symptoms while gathering demographic information. A total of 600 Tibetan residents from the Dege area of Garze Prefecture, Sichuan, China, participated in the survey. The mean age is 56.81 years, males comprising 52.8% and females 47.2% of the sample. Of the participants, 41.2% resided permanently at elevations exceeding 3500 m. The results found that the weighted prevalence of depression in the area was 24.62%. Regardless of gender, the age group with the highest prevalence was 55–64 years old. Depression increased with age as well as gradually decreased after the age of 60. Logistic regression analysis showed that middle-aged (OR 2.86, 95% CI 1.69–4.82, P < 0.01) and elderly people (OR 2.27, 95% CI 1.30–3.98, P < 0.01), living in ultra-high altitude areas (OR 3.48, 95% CI 1.35–2.91, P < 0.01) and low BMI (OR   4.31, 95% CI 1.33–13.93) are high-risk factors for depression. This study enhances the understanding of the characteristics of depression in high-altitude regions of China, contributing to a more comprehensive view of the psychological well-being of residents in these areas. The findings underscore the need for targeted prevention and treatment strategies tailored to the specific needs of these populations.